Rancang Bangun Generator Sebagai Sumber Energi Listrik Nanohidro - Abdan Sakura; Amir Supriyanto; Arif Surtono (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2017)
Generator design has been realized as a source of electricity energy nanohidro using 6 pairs of poles of permanent magnets and copper coils to 6 pairs of windings tool created to generate power nanohidro dam waterfall flows to the load 210 watt. Batu Putu designed tool able to work constantly for rotating turbines. Design to manufacture rotor and stator circuits mounted on prime mover induction motor. The test results showed that the greater the speed of the voltage and current produced water increases. Testing is done with a multimeter instrument and tachometer first appliance testing done in 1 day 5 hours produces the light on the data obtained average voltage - current average of 128,92V and was unchanged at 1.69 A.